Pengaruh Desain Stent pada Jumlah Limfosit dan Trombosit Kelinci (Oryctolagus Cuniculus) - Widowati Siswomihardjo; Dyah Anindya Widyasrini; Dinar Arifianto; Setyo Budhi; Nahar Taufiq (Jurnal Teknosains, 2019)
Percutaneous Coronary Intervention (PCI) is an effective treatment for coronary artery diseases. For the procedure, a stent is put in the coronary arteries. There are a variety of stent materials and designs available on the market. The development of stents continues with the goal to reduce the risk of failure. The design and the ability of the stent as a vascular scaffold are important factors for the success of the stent. The implantation of a stent as a foreign body can lead to inflammation. In general, the inflammation is characterized by an increased number of lymphocytes. Then, platelets play a role in coordinating the occurrence of inflammation and immune response. This study aims to determine the effect of stent design on the number of lymphocytes and platelets as a marker of inflammation. The study was conducted on ten rabbits divided into two treatment groups, namely KP1 (new design stent) and KP2 (commercial stent) by placing a stent on the iliac artery. One hour before stenting, 2 ml of blood was collected in all experimental animals. Then, 2 ml of blood was collected again on the 7th and 28th day after stenting.  Data was collected based on the number of lymphocytes and platelets from all experimental animals. Statistical analysis using two-way ANOVA shows no significant difference (p> 0.05) on the number of lymphocytes and platelets between the two groups with different stent designs. It can be concluded that the design of a stent does not show a tendency to cause inflammation.